2016
DOI: 10.1177/1753193415622760
|View full text |Cite
|
Sign up to set email alerts
|

From the brachial plexus to the hand, multiple connections between the median and ulnar nerves may serve as bypass routes for nerve fibres

Abstract: Axons from the median and ulnar nerves can pass to each other through aberrant connections between them. Multiple interconnections between the nerves may provide a detour route for nerve fibres going to the hand. We investigated the incidence of variations and the associations between them in 90 cadaveric upper limbs. In 91% of upper limbs, one to five variations were found, with several statistically significant associations. The contribution of the C8 nerve to the lateral cord was positively associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 26 publications
0
24
0
6
Order By: Relevance
“…Some of this variation is thought to be due to connections between the Median and Ulnar nerves, such as the Riche -Cannieu anastomosis discussed below. In approximately 2% of hands the Ulnar nerve was found to innervate all the thenar muscles, and the Adductor Pollicis [2,56,70]. One author found that the median nerve solely innervated the thenar muscles in roughly one quarter of the population [22].…”
Section: Thenar Muscles and The Adductor Pollicismentioning
confidence: 99%
See 3 more Smart Citations
“…Some of this variation is thought to be due to connections between the Median and Ulnar nerves, such as the Riche -Cannieu anastomosis discussed below. In approximately 2% of hands the Ulnar nerve was found to innervate all the thenar muscles, and the Adductor Pollicis [2,56,70]. One author found that the median nerve solely innervated the thenar muscles in roughly one quarter of the population [22].…”
Section: Thenar Muscles and The Adductor Pollicismentioning
confidence: 99%
“…The MGA is formed in the forearm by an anastomosis between either the Anterior Interosseous Nerve or the main body of the Median nerve, to the Ulnar nerve [12,13,26,45,53,70]. The nerve axons start in the proximal Median nerve and cross the forearm to join the distal Ulnar nerve [70]. This anastomosis often carries motor fibers and has been shown to alter the innervation of the hand [12,20,42].…”
Section: Martin Gruber Anastomosis (Mga)mentioning
confidence: 99%
See 2 more Smart Citations
“…These authors emphasized that the incidence of CRA could potentially be higher if finer dissection techniques and fresh cadavers were used to avoid missing the smaller anastomotic fibers. According to Yang et al (2016), CRAs were observed in 45 of 90 cadaveric upper limbs (50 %).…”
Section: Discussionmentioning
confidence: 99%